PENGARUH SANAD ‘ALÎ TERHADAP AUTENTISITAS HADIS: STUDI HADIS THULÂTHIYÂT SUNAN IBN MÂJAH - Mahdi, Fahrizal (Program Studi Perbandingan Agama, Fakultas Ushuluddin dan Filsafat, Universitas Islam Negeri (UIN) Sunan Ampel Surabaya, 2016)
This article aims to explain the influence of sanad ?alî on the quality of hadis. Sanad is one of the most important elements in determining the authenticity of hadis. Therefore, the scholars were going (ri?lah) to Mecca, Madinah, Egypt, Baghdad, Sham, ?urasân and other regions to listen the hadis directly from the authoritative sources and to obtain higher level of the chain (al-isnâd al-?âlî). Imâm Ibn Mâjah has collected five hadis thulâthî and these five hadis are narrated from the only one sanad that is Jubârah b. al-Mughallis from Kathîr b. Sulaym from Anas b. Mâlik. By applying historical approach to observe narrators? background, this article, then, argues that the construction of al-isnâd al-?âlî can avoid defects probability in the case of al-isnâd al-nâzil (sanad with several narrators). The al-isnâd al-?âlî encourages the scholars of hadis to confirm hadis by leaving al-isnâd al-nâzil. However, there is no certainty of the authenticity of a hadis, because the defects which appears in al-isnâd al-nâzil, can also occur in al-isnâd al-?âlî